Design and Synthesis of Polycycles, Heterocycles, and Macrocycles via Strategic Utilization of Ring‐Closing Metathesis. Issue 11 (19th June 2018) - Kotha, Sambasivarao; Meshram, Milind; Dommaraju, Yuvaraj
Abstract: In this perspective, we summarize new synthetic approaches for the construction of various polycyclic compounds involving ring‐closing metathesis as a key step. In this regard, we used ring‐closing metathesis in combination with other popular reactions like Suzuki‐Miyaura coupling, Claisen rearrangement, Fischer indolization, Grignard addition, Diels‐Alder reaction, and [2+2] cycloaddition reaction etc. To this end, a variety of functional molecules such as α‐amino acids, cyclophanes, heterocycles, propellanes, spirocycles, and macrocycles have been prepared. The strategies developed and the molecules prepared here play a key role in designing new materials and also act as lead compounds in drug design. The strategies and tactics developed here are useful to design polycycles, macrocycles, and heterocycles of diverse ring systems. Abstract : In this report, we have reviewed various synthetic approaches for the construction of polycyclic compounds via ring‐closing metathesis (RCM) as a key step. RCM protocol with other popular reactions such as Suzuki‐Miyaura coupling, Claisen rearrangement, Fischer indolization, Grignard addition, Diels‐Alder reaction, and [2+2] cycloaddition reaction was employed for the synthesis of a wide variety of intricate molecules.